2023
DOI: 10.1186/s40164-023-00427-w
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: a novel regulated cell death participating in cellular stress response, radiotherapy, and immunotherapy

Abstract: Background Ferroptosis is a regulated cell death mode triggered by iron-dependent toxic membrane lipid peroxidation. As a novel cell death modality that is morphologically and mechanistically different from other forms of cell death, such as apoptosis and necrosis, ferroptosis has attracted extensive attention due to its association with various diseases. Evidence on ferroptosis as a potential therapeutic strategy has accumulated with the rapid growth of research on targeting ferroptosis for tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 205 publications
0
8
0
Order By: Relevance
“…Ferroptosis, a novel form of cell death characterized by GSH depletion and lipid peroxidation [ 45 47 ], has gained attention due to its close association with various cancers [ 48 ]. Our RNA-seq analysis revealed that the combination therapy enriched pathways related to oxidative stress, GSH metabolism, and p53.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, a novel form of cell death characterized by GSH depletion and lipid peroxidation [ 45 47 ], has gained attention due to its close association with various cancers [ 48 ]. Our RNA-seq analysis revealed that the combination therapy enriched pathways related to oxidative stress, GSH metabolism, and p53.…”
Section: Discussionmentioning
confidence: 99%
“…In mice and humans, distinct GPX4 isoforms with different subcellular localization are known to be produced through alternative splicing and transcription initiation; cytoplasmic GPX4, mitochondrial GPX4 (mGPX4), and nuclear GPX4 (nGPX4) [30]. The cytoplasmic GPX4 is the isoform essential for cell survival and prevention of lipid peroxidation and ferroptosis cell death [31,32]. Together, our data suggests that virulent IOE infection not only interferes with the nuclear translocation and activation of NRF2, but also with the stability of cytoplasmic NRF2, which is associated with significant downregulation of cytoplasmic GPX4 and antioxidant response.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Ferroptosis is unique in its capacity to target metabolic pathways other than those addressed by immunotherapy. This could provide an alternate or complementary option to current treatments, particularly when immunotherapy fails [ 26 , 27 ]. In addition, leukemia cells are more likely to express transferrin and contain more iron than other tumor cells, which makes it easier for ROS to accumulate in leukemia cells and trigger ferroptosis.…”
Section: Introductionmentioning
confidence: 99%